2022
DOI: 10.3389/fnagi.2022.863901
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the FNDC5/Irisin on Elderly Dementia and Cognitive Impairment

Abstract: Population aging is an inevitable problem nowadays, and the elderly are going through a lot of geriatric symptoms, especially cognitive impairment. Irisin, an exercise-stimulating cleaved product from transmembrane fibronectin type III domain-containing protein 5 (FNDC5), has been linked with favorable effects on many metabolic diseases. Recently, mounting studies also highlighted the neuroprotective effects of irisin on dementia. The current evidence remains uncertain, and few clinical trials have been undert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 143 publications
0
14
0
Order By: Relevance
“…Uncontrolled hippocampal damage can cause serious cognitive deficits [ 3 ]. Previous studies have highlighted the protective effects of Fndc5/irisin on synaptic plasticity [ 38 ], neuroinflammation [ 14 ] and cognitive function [ 39 ]. We further investigated the potential roles of hippocampal Fndc5/irisin in experimental VaD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Uncontrolled hippocampal damage can cause serious cognitive deficits [ 3 ]. Previous studies have highlighted the protective effects of Fndc5/irisin on synaptic plasticity [ 38 ], neuroinflammation [ 14 ] and cognitive function [ 39 ]. We further investigated the potential roles of hippocampal Fndc5/irisin in experimental VaD.…”
Section: Resultsmentioning
confidence: 99%
“…These data suggested CCH destroys the activity of Fndc5/irisin in brain, especially in the hippocampal region, this pathological process may be accelerated or aggravated by age burden. Moreover, accumulating evidences had highlighted the positive strategy of rescuing or improving the signaling pathway activity of brain Fndc5/irisin in dementia prevention and treatment [ 39 , 47 ]. Excitingly, we further demonstrated that boosting hippocampal Fndc5/irisin improves the synaptic plasticity of ischemic neurons and the inflammatory microenvironment in hippocampus, and then reduces the cognitive deficits in BCAS mice.…”
Section: Discussionmentioning
confidence: 99%
“…Exacerbated inflammatory responses have been linked to the development of AD 20 and depression, 21 and the beneficial effects of exercise and irisin are, at least in part, thought to involve an attenuation of inflammation. 8,33,46,47,55 Lipoxin A4 is a lipid mediator involved in the resolution of inflammatory responses 22 and found to be reduced in the CSF and hippocampi of AD patients. 9 Our results show that CSF lipoxin A4 is lower in subjects with depression, both with and without cognitive impairment, compared to individuals without depression of similar age (120.6 pg/mL vs 48.5 pg/mL, difference between medians = -72.1 pg/mL [95% CI, −90.28 to -21.34]; p = 0.001) (Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
“…Because irisin and BDNF can modulate inflammatory processes, 8,46,47 Brazilian cohort similar to the one used in the current study. 48 Third, due to the lack of a quantitative measure of physical activity, we could not include physical exercise as a covariate in our analyses.…”
Section: Results Implications and Limitations Of The Studymentioning
confidence: 99%
“…Irisin, a myokine derived from FNDC5, also acts through PGC-1α and passes through the BBB to increase BDNF expression and enhance learning, memory, and mood [12]. FNDC5/irisin acts as a messenger of muscle-brain crosstalk, in uencing neurogenesis in people with cognitive impairment, particularly through the neuroprotective effects of BDNF [27]. In the CNS, irisin causes neurogenesis and particularly the differentiation of stem cells into neurons in the hippocampus [28].…”
Section: Discussionmentioning
confidence: 99%